SELF-EFFICACY AND METACOGNITION AS MEDIATING EFFECTS OF GROWTH MINDSET ON STUDENTS’ WRITING SKILLS - Amrina; Syarifatul Hayati Zarfi; Daniyar Satybaldy (Journal International of Lingua and Technology, 2025)
In the field of education, writing skills represent a vital competency that university students must possess. These skills are closely interrelated with self-efficacy and metacognition. Self-efficacy refers to an individual’s belief in their capability to execute the actions required to achieve specific goals, while metacognition involves an individual’s awareness of their own thinking processes. Both elements are essential for the development of effective writing proficiency. This study aims to examine and observe students’ writing skills, which are crucial for academic success in higher education, as an effort to analyze the mediating effects of a growth mindset on students’ writing performance. This research employs a quantitative method using a survey design. Data were collected via questionnaires distributed to a sample of students from the Arabic Language Education and English Language Education programs at the State Islamic University (UIN) Mahmud Yunus Batusangkar. Data were analyzed using mediation analysis techniques. The findings indicate that self-efficacy and metacognition significantly function as mediating variables in the relationship between a growth mindset and students’ writing skills. These components are proven to be fundamental factors in the educational process. This study demonstrates that writing skill is a critical competence for students. A growth mindset enhances self-efficacy and metacognitive awareness, both of which strongly influence writing effectiveness. When students possess the ability to write effectively, they feel more confident in their abilities. Furthermore, when students utilize metacognitive awareness to construct their writing alongside high self-efficacy, they experience a significant improvement in their overall writing skills.